Assessing public health needs in a lower middle income country - Ruel-Burgeron, Sarah (Routledge focus on environmental health, 2021)
"This book demonstrates a methodology for assessing public health needs in communities experiencing environmental sanitation inadequacies. Centring on a case study of the Republic of Cameroon, the findings represent the starting point of a campaign to implement a comprehensive water and sanitation infrastructure through advocacy, housing improvements, and new service chains. This book should appeal to environmental health professionals, academics and policymakers, be they domestic to the African region or multinational practitioners"--